2007
DOI: 10.3758/bf03193774
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between covert and overt attention in endogenous cuing

Abstract: developed the now classic cuing technique for manipulating spatial attention independently of eye movements. In this paradigm, participants typically have to detect or discriminate a target and respond manually by pressing the appropriate response key. The target stimulus is preceded by a cue that provides information about the location of the upcoming target. In a cuing version typically referred to as endogenous, a centrally displayed arrow points to the likely target location. Participants are instructed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 74 publications
(107 reference statements)
2
36
0
Order By: Relevance
“…The oculomotor system was suppressed, but it was not neutral in relationship to attentional allocation, as would be expected under the independence account. A relevant result has recently been reported by Van der Stigchel and Theeuwes (2007), who showed that saccades deviated away from the locations where endogenous attention was maintained. It was proposed that endogenous attention resulted in activation in the oculomotor system that had to be inhibited in order for an eye movement in a different direction to be made (see also Sheliga, Riggio, & Rizzolatti, 1995).…”
Section: Discussionsupporting
confidence: 58%
“…The oculomotor system was suppressed, but it was not neutral in relationship to attentional allocation, as would be expected under the independence account. A relevant result has recently been reported by Van der Stigchel and Theeuwes (2007), who showed that saccades deviated away from the locations where endogenous attention was maintained. It was proposed that endogenous attention resulted in activation in the oculomotor system that had to be inhibited in order for an eye movement in a different direction to be made (see also Sheliga, Riggio, & Rizzolatti, 1995).…”
Section: Discussionsupporting
confidence: 58%
“…It is thus possible that the benefits seen in covert orienting tasks will not extend to an overt orienting task, since covert and overt attentional systems may be separable when eye movements are withheld and attention is allocated covertly (Hunt & Kingstone, 2003a, 2003bKlein, 1980). That said, the general consensus is that when eye movements are executed, covert and overt shifts of attention are tightly linked, such that covert shifts precede overt shifts of attention (Hoffman & Subramaniam, 1995;Moore & Fallah, 2001; Van der Stigchel & Theeuwes, 2007). Therefore, it is reasonable to expect that the AVGP covert attention advantage will extend to overt attentional orienting.…”
mentioning
confidence: 99%
“…1 There is a growing body of evidence that the visuospatial attention system and the oculomotor system are tightly linked. For example, a covert shift of attention to a location is accompanied by the preparation of an eye movement to that location (Belopolsky & Theeuwes, 2009;Van der Stigchel & Theeuwes, 2007). Also, covert shifts of attention activate brain regions that are nearly identical to those activated by saccadic eye movements (de Haan, Morgan, & Rorden, 2008;Ikkai & Curtis, 2008).…”
Section: Introductionmentioning
confidence: 98%